A fairy-tail ending - Mann, Catherine (Harlequin special edition, 2024)
Sure, Isobel Dalton is entranced by the handsome man dressed as a pirate for her daughter's sixth birthday. But firefighter Cash Warner is a man with his own physical and emotional scars -- hardly an angel in disguise. When an unexpected inheritance much needed for her child's kidney transplant comes in the form of a family mystery at the Top Dog Dude Ranch, Cash insists on tagging along... evoking desire and tearing down Isobel's emotional walls in the process. Could the hardened, wounded, irresistible man be the miracle she's prayed for all along?